1996
DOI: 10.1099/00221287-142-4-937
|View full text |Cite
|
Sign up to set email alerts
|

Stress tolerance and pathogenic potential of a mannitol mutant of Cryptococcus neoformans

Abstract: Cryptococcus neoformans produces large amounts of the acyclic hexitol mannitol in culture and infected animals, but the functional and pathogenic significance of mannitol production by this fungus is not known. We exposed C. neoformans H99 (Cn H99) to UV irradiation (1 x LD, , ) and screened survivors for mannitol production. A mutant, Cn MLP (Mannitol Low Producer), synthesized less mannitol from glucose (2.7 vs 8-2 nmol per lo8 cells min-' a t 37 "C) and contained less intracellular mannitol (1 vs 11 pmol pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 18 publications
1
68
0
Order By: Relevance
“…Although this result implies that inability to express MPD mRNA was not responsible for mannitol underproduction in C. neoformans MLP, we have not ruled out a loss of function mutation in the gene encoding MPD in C. neoformans MLP. Lastly, because earlier studies suggested that mannitol may function in C. neoformans as an intracellular stress protectant (Chaturvedi et al, 1996a), we also examined MPD mRNA levels in C. neoformans cells exposed to temperature and osmotic stresses and we found that MPD mRNA levels increased when C. neoformans was cultured in YPD supplemented with 0n2 or 0n4 M NaCl (but not higher levels) and when the incubation temperature was increased from 25 mC to 30 mC or 37 mC.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although this result implies that inability to express MPD mRNA was not responsible for mannitol underproduction in C. neoformans MLP, we have not ruled out a loss of function mutation in the gene encoding MPD in C. neoformans MLP. Lastly, because earlier studies suggested that mannitol may function in C. neoformans as an intracellular stress protectant (Chaturvedi et al, 1996a), we also examined MPD mRNA levels in C. neoformans cells exposed to temperature and osmotic stresses and we found that MPD mRNA levels increased when C. neoformans was cultured in YPD supplemented with 0n2 or 0n4 M NaCl (but not higher levels) and when the incubation temperature was increased from 25 mC to 30 mC or 37 mC.…”
Section: Discussionmentioning
confidence: 97%
“…C. neoformans strains H99 (wild-type, serotype A) and MLP (a UV-generated mutant of strain H99 that underproduced and underaccumulated mannitol) (Wong et al, 1990 ;Chaturvedi et al, 1996a) were cultured in YPD (1 % yeast extract, 2 % peptone, 2 % glucose) or synthetic complete medium (0n67 %, w\v, yeast nitrogen base with amino acids) containing either 2 % glucose or 2 % mannitol. Saccharomyces cerevisiae YPH252 (Matα ura3-52 lys2-801 ade2-101 trp1-1∆ his3-∆200) and YPH252 gpd1∆ ::leu2 (Eriksson et al, 1995) were cultured in YPD, and uracil prototrophs were cultured in synthetic complete (SC) medium containing 2 % (w\v) glucose but no uracil (SC glukura) or in SC medium containing 2 % (w\v) galactose but no uracil (SC galkura).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of mannitol in fungi is unclear but it has recently been suggested [17] that mannitol is important to the pathogenicity of the fungus Cryptococcus neoformans in mice, aiding in the tolerance to heat and osmotic stress. In Eimeria, the most apparent role of this pathway is in the development and maturation of oocysts [15,16].…”
mentioning
confidence: 99%
“…melanin and capsule production, mannitol utilization etc. (Chaturvedi et al, 1996) in C. neoformans are unique to certain geophilic group among the whole of the fungal community. Decoding of the 'adaptive ability' of these fungi would definitely provide a better management strategy for containing the diseases caused by them.…”
Section: Introductionmentioning
confidence: 99%